A Bibliometric Study of Worldwide Trends in Teaching Fiction in English Literature - Rizka Safriyani; Muhammad Farid Ubaidillah; Siti Uswatun Khasanah (English Education Department, 2026)
This study employs bibliometric analysis to map international trends in teaching fiction in English literature classrooms, including trends in publication, major scholars, and emerging themes. According to the Scopus database statistics, research papers published from 2010 to 2024 were queried with the terms